Caracterização genotípica de rizóbios e eficiência simbiótica em estilosantes (Stylosanthes spp.) - Chaves, Josimar da Silva (2018)
Stylosanthes is a forage legume found in several regions of Brazil wchich establish symbiosis with rhizobia, being an alternative to improve the soil fertility in pastures. Despite its importance as forage, there is lack in studies regarding diversity of native rhizobia on symbiosis with this legume. Likewise, studies of symbiotic efficiency through the inoculation of rhizobia are also scarce, with most of them conducted in Australia. In this way, the objective of the study was to evaluate the genetic diversity and symbiotic efficiency of nitrogen fixing bacteria, isolated from Stylosanthes ssp. collected in savanna areas in Roraima.We used 28 isolates from the Embrapa Roraima Collection of Functional Microorganisms. Diversity was assessed through genotypic characterization, using 16S rRNA, nodC and housekeeping genes (recA, gyrB and glnII) sequence. To evaluate symbiotic efficiency, experiments were conducted under greenhouse and under field conditions using Stylosanthes cv. Campo Grande. A large diversity of nodulating bacteria were found, including both α-Proteobacteria and β-Proteobacteria, notably the genera Bradyrhizobium, Rhizobium, Mesorhizobium and Burkholderia. Two strains recommended for Stylosanthes ssp., BR 446 and BR 502, proved to be efficient in the BNF process under all tests. The isolates ERR 917, ERR 922 and ERR 1173 showed potential to contribute to the growth of Stylosanthes plants, providing results similar to the two strains currently recommended for this legume in the all variables analyzed. The inoculation promoted an increase of N in the soil-plant system, equivalent to 30 kg of N ha-1, influencing positively the biomass production. The inoculation with the best strains provides a significant increase in plant dry matter, with values above 4000 kg ha-1, and accumulation of N derived from BNF, which may exceed 50 kg ha-1, in comparison to the uninoculated control.